Cycling Quiescence in Temozolomide Resistant Glioblastoma Cells Is Partly Explained by microRNA-93 and -193-Mediated Decrease of Cyclin D - Munoz, Jessian L.; Walker, Nykia D.; Mareedu, Satvik; Pamarthi, Sri Harika; Sinha, Garima; Greco, Steven J.; Rameshwar, Pranela (Frontiers in Pharmacology, 2019)
Glioblastoma (GBM) is a fatal malignancy of the central nervous system, commonly associated with chemoresistance. The alkylating agent Temozolomide (TMZ) is the front-line chemotherapeutic agent and has undergone intense studies on resistance. These studies reported on mismatch repair gene upregulation, ABC-targeted drug efflux, and cell cycle alterations. The mechanism by which TMZ induces cell cycle arrest has not been well-established. TMZ-resistant GBM cells have been linked to microRNA (miRNA) and exosomes. A cell cycle miRNA array identified distinct miRNAs only in exosomes from TMZ-resistant GBM cell lines and primary spheres. We narrowed the miRs to miR-93 and -193 and showed in computational analyses that they could target Cyclin D1. Since Cyclin D1 is a major regulator of cell cycle progression, we performed cause-effect studies and showed a blunting effects of miR-93 and -193 in Cyclin D1 expression. These two miRs also decreased cell cycling quiescence and induced resistance to TMZ. Taken together, our data provide a mechanism by which GBM cells can exhibit TMZ-induced resistance through miRNA targeting of Cyclin D1. The data provide a number of therapeutic approaches to reverse chemoresistance at the miRNA, exosomal and cell cycle points.